(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The article studies the prevalence and extent of slaveryin the 19th century India. It looks at the various ways and meansthrough which slave servitude was perpetuated. It also discusses the variousaspects of slavery and its legitimizing factors such as caste relations,indebtedness and also contract. The article also delves into regulation ofslavery in India through several legislative interventions and finally analysesthe continuation of slavery under the garb of debt-bondage and forced contractlabour.